Efficiency of the Current System of Remuneration in the Public Sector - D. Novokreshchenova (Taras Shevchenko National University of Kyiv, 2022)
The range of public sector entities was defined in accordance with the effective legislation. The current remuneration in the public sector was studied, that allowed to identify the system’s main problems. Also, the main aspects were summarized that must be considered when reforming remuneration costs in the public sector, particularly in budgetary institutions. The difference in the interpretation of the categories “remuneration” and “wages” is considered. The structure of the general public management sector and the structure of the employee benefits fund were approved by the salary statistics instruction and were graphically depicted. The forms and systems of the wage fund and the structure of remuneration in the public sector are considered. The reform of the remuneration system in public sector is analyzed and ways for its improvement are proposed. Public demand for high-quality and highly qualified public service posed many problems for the public administration system. Indispensable changes in the principles and approaches to public management begin with motivated, depoliticized specialists capable of qualitatively performing the assigned tasks. One of the critical factors in forming such motivation is the projected remuneration system. On the other hand, the lack of stability and predictability of remuneration leads to low-quality public administration and politicization. The paper explores the mechanisms of politicization of civil service through remuneration and analyzes the legal framework for calculating remuneration and in-depth interviews with civil servants regarding their motivation.

Визначено коло суб'єктів державного сектору відповідно до чинного законодавства. Проведено дослідження сучасного стану чинної системи оплати праці в державному секторі, на основі чого виокремлено основні проблеми системи оплати праці, також узагальнено основні аспекти, які необхідно враховувати під час реформування видатків на оплату праці в державному секторі, зокрема в установах бюджетної сфери. Розглянуто різницю у трактуванні категорій "оплата праці" та "заробітна плата". Графічно зображено структуру сектору загального державного управління, структуру фонду оплати праці, затверджену інструкцією зі статистики заробітної плати. Розглянуто форми та системи оплати праці та структуру винагороди за працю у державному секторі. Проаналізовано реформування системи оплати праці працівників державного сектору та запропоновано напрями її удосконалення.
Ефективність чинної системи оплати праці в державному секторі
Keywords: фонд оплати праці; реформа; державні службовці; національні стандарти4 державний сектор; ефективність; wage fund; reform; public sector employees; national standards; public sector; and efficiency